Experiences of using vedolizumab in the treatment of inflammatory bowel disease in the East Midlands UK – a retrospective observational study. (2nd August 2020) - White, Jonathan R.; Din, Said; Ingram, Richard J. M.; Foley, Stephen; Alam, Mohammad Aftab; Robinson, Richard; Francis, Rodric; Tucker, Emily; Jalal, Mustafa; Elphick, David; Atallah, Edmond; Norman, Anthony; et al.
Abstract: Purpose: Clinical trials have demonstrated efficacy of vedolizumab in ulcerative colitis (UC) and Crohn's disease (CD). Further real-world data is needed to inform clinical practice. The primary outcome was to assess corticosteroid-free and clinical remission after vedolizumab initiation. Secondary outcomes included effect on disease activity scores, biochemical markers, concomitant drug use, endoscopic remission, surgical intervention, hospital admissions and adverse events. Materials and methods: A multi-centre retrospective observational study was conducted with patients initiated on vedolizumab across seven UK hospitals 1/11/14-30/11/16. Clinical disease activity was assessed using the partial Mayo Scores (pMS) and Harvey Bradshaw Index (HBI). Clinical remission was defined as HBI ≤4 or pMS <2 with a combined stool frequency and rectal bleeding sub score of ≤1. Clinical response was defined as ≥2-point decrease from baseline in pMS and ≥3-point decrease from baseline in HBI. Results: One hundred ninety-two patients were included in the final analysis. 45% of UC and 10% of CD patients were anti-TNF naive. Over the observation period corticosteroid-free remission rates for UC and CD were 46% and 45%, while clinical remission rates were 52% and 44%, respectively. Time to corticosteroid free remission for UC and CD was 17.6 [IQR: 8.7–29.6] and 14.1 [QR: 6.0–21.7] weeks, respectively. Time to clinical response for UC was 9.4 [IQR: 5.7–15.4] and CD was 9.5 [IQR: 6.1–18.2] weeks. There was a substantial decrease in the concomitant use of immunomodulators and a similar decrease in concomitant corticosteroid use over the study period. Conclusions: Results in this predominately anti-TNF experienced population mirror other published real-world data, demonstrating good clinical effectiveness and a comparable safety profile.